Is the Care System to Blame for the Poor Educational Outcomes of Children Looked After? Evidence from a Systematic Review and National Database Analysis. (1st June 2018) - Luke, Nikki; O'Higgins, Aoife
Abstract : It is recognised internationally that children in out-of-home care ('children in care' or 'children looked after') generally have lower educational attainments than other pupils. This article provides two forms of evidence that challenge the view that care status in itself can explain this 'attainment gap'. A systematic review of 28 studies was conducted to assess the evidence on whether being in care is detrimental to young people's educational outcomes. This is complemented by an analysis of administrative data from England, which compares the educational outcomes of children in care at age 16 to those of children in the general population and to other children supported by social services. Taken together, the findings suggest that while research demonstrates an important attainment gap between children in care and children in the general population, this difference is reduced and in many cases disappears when other important factors are taken into consideration to reduce selection bias. We find little evidence that being in care is detrimental to the educational outcomes of children looked after, but suggest that given the heterogeneity of the population, special attention should be paid to different groups of children and their particular needs while in care.